Review of control options for elm leaf beetle, Xanthogaleruca luteola Müller, with a focus on Australia. Issue 1 (3rd July 2022) - Dominiak, Bernard C.; Kidston, Jenene
ABSTRACT: Elm leaf beetle (ELB) is a comparatively new invader in south-eastern Australia. ELB can cause considerable defoliation and adversely impact tree health. Here, we conducted a literature review and found a range of control measures. We found two main biological control insects, Oomyzus gallerucae and Erynniopsis antennata, but they rarely adequately control ELB populations or prevent considerable defoliation. We report on more than 20 insecticides used to control ELB, primarily consisting of organophosphates, pyrethroids and neonicotinoids. There is no ideal insecticide as some very effective insecticides have environmental or human health concerns. Products based on azadirachtin or similar compounds seem to generate least concerns and are insect specific, but may have short residues. The choice of insecticidal intervention will be based on issues pertinent to each situation and many pesticide options are available.